2019
DOI: 10.1186/s12874-019-0674-3
|View full text |Cite
|
Sign up to set email alerts
|

The key therapeutic factors needed to deliver behavioural change interventions to decrease risky substance use (drug and alcohol) for looked after children and care leavers: a qualitative exploration with young people, carers and front line workers

Abstract: Background Looked after children and care leavers have an increased risk of drug and alcohol use compared to their non-LAC peers. Despite high prevalence rates within this population, looked after children are reported to show low levels of engagement in services resulting in unmet needs emerging from substance use. This paper reports on the initial formative phase of a pilot feasibility randomised controlled trial; SOLID ( S upp o rting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Young people in care are an under-researched group and there are well-known challenges in conducting trials in this group, including the lack of research infrastructure in Social Care [47]. We undertook extensive formative work, adapted interventions with young people in care and relevant staff [19] and then conducted a pilot trial and parallel process evaluation. Despite the detailed preparatory work, we found that is it not feasible to conduct a trial of the adapted substance use behaviour change interventions within the current screening, referral and treatment pathway.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Young people in care are an under-researched group and there are well-known challenges in conducting trials in this group, including the lack of research infrastructure in Social Care [47]. We undertook extensive formative work, adapted interventions with young people in care and relevant staff [19] and then conducted a pilot trial and parallel process evaluation. Despite the detailed preparatory work, we found that is it not feasible to conduct a trial of the adapted substance use behaviour change interventions within the current screening, referral and treatment pathway.…”
Section: Discussionmentioning
confidence: 99%
“…25 questions to assess four difficulty subscales and measure pro-social behaviour. Total difficulties scores range from 0-40, each one-point increase in this score corresponds with an increased risk of developing mental health disorders; close to average (0-14), slightly raised (15)(16)(17), high (18)(19), very high (20-40).…”
Section: Strengths and Difficultiesmentioning
confidence: 99%
See 3 more Smart Citations